A comparative study of various techniques of incisional hernia repair in a tertiary care center at Bikaner (North-West Rajasthan) - Singh, Bhal; Jalthania, Mahender Kumar; Kumari, Santosh (International Surgery Journal, 2019)
Background: Incisional hernia can be defined as an internal abdominal wall defect that develops after a previously closed laparotomy. Aim of present study was to compare open suture repair and mesh repair (onlay and sublay), various factors predisposing to incisional hernia and evaluate complications following surgery for incisional hernias. Methods: A prospective study was conducted in 60 cases of incisional hernia admitted in Department of General Surgery, PBM Hospital Bikaner between October 2017 to September 2018. 20 cases were selected in each group (open anatomical repair, onlay mesh repair and sublay mesh repair). All cases were followed up for 6 months postoperatively. Results: Incisional hernia was found to occur more often in 41-60 years age group (61.67%) and in females. Wound infection (46.67%) after index surgery was most important risk factor followed by obesity. LSCS (30%) was found to be most common index surgery followed by hysterectomy (28.33%). Seroma was most common postoperative complication (5% patient in anatomical repair group, 30% patients in onlay group and 10% patients in sublay group).Only one recurrence (5%) was observed in anatomical repair group over a period of 6 months follow up. Conclusions: Sublay mesh repair is superior to onlay mesh repair and Anatomical suture repair regarding recurrence rate. Local postoperative complications like seroma formation or wound infection were more common in mesh repair surgery than anatomical repair. Among mesh repair these complications were higher in onlay group than sublay repair.